Влияние холецистита на уровень билирубина в сыворотке крови - Niiazova N. D., Beishenalieva S. T. (Scientific studies: from theory to practice, 2017)
Аnnotation:The paper presents the research on the impact of cholecystitis in the blood serum level in the body of patients with acute and chronic cholecystitis. It is shown that in all age groups surveyed in the body of patients with cholecystitis cause hyperbilirubinemia
Keywords: печень; билирубин; холецистит; желчный пузырь; Keywords: liver; cholecystitis; bilirubin; gall bladder